Extended jacobi matrix polynomials - Aktaş, Rabıa; Çekim, Bayram; Çevik, Ali (Utilitas Mathematica, 2013)
In this paper, extended Jacobi matrix polynomials (EJMPs) are introduced. The matrix differential equation satisfied by them is given. A Rodrigues formula, orthogonality, linear generating matrix functions and recurrence relations are presented for these matrix polynomials. Furthermore, general families of multilinear and multilateral generating matrix functions are obtained and their applications are presented.